(untitled) (Research, Society and Development, 2020)
In this work, the objective was to correlate anisotropy with the mechanical and microstructural behavior of two high strength steels used in vehicle production in order to obtain variables to alter future manufacturing processes in order to obtain steels with a lower elastic return, known as springback effect, which means geometric changes suffered by the part at the end of the plastic deformation process, after the release of the forces applied by the stamping tool and this causes dimensional failures that compromise the production. In this research, biphasic steel and one low carbon steel were evaluated, being Docol_DL800 and LC200 their trade names, respectively. Tensile tests and three-point bending in air were performed to determine the mechanical properties and behaviors and these results were compared with those obtained by computational simulation using the finite element method and were also correlated with microstructural data from the backscattered electron technique. The results indicate that biphasic steel has a higher hardening allowing a greater springback effect due to its microstructure with ferrite and martensite, high grain refinement, greater amount of elastic residual energy and a lower degree of disorientation after mechanical conformation, creating the effect Bauschinger. Already the steel LC200 presented a smaller degree of springback thanks to the more isotropic hardening due to the increase in the degree of grain disorientation after the conformation. Thus, it was concluded that the manufacturing processes of these steels should seek to combine high mechanical strength with a more isotropic behavior.